The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/2050313x211057700
|View full text |Cite
|
Sign up to set email alerts
|

Superior Vena Cava Syndrome due to pericardial hematoma: A case report and mini-review of literature

Abstract: Superior vena cava syndrome is a life-threatening condition. Typically, the clinical presentations are gradual; hence, the diagnosis is often delayed until critical compression or obstruction has occurred. Pericardial hematoma is a rare condition that could occur after cardiac surgery. An asymptomatic, 25-year-old female, who underwent surgical atrial septal defect closure 5 days ago, was sent for routine echocardiography examination before discharge. An intrapericardiac hematoma was detected at the right atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Mediastinal hematoma caused due to damage from epicardial wires of CABG is an uncommon but significant complication [4,5]. Mediastinal hematoma with sufficient volume may result in compression of the neighboring heart chambers or vessels, one of which could be superior vena cava leading to the superior vena cava syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mediastinal hematoma caused due to damage from epicardial wires of CABG is an uncommon but significant complication [4,5]. Mediastinal hematoma with sufficient volume may result in compression of the neighboring heart chambers or vessels, one of which could be superior vena cava leading to the superior vena cava syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…The computed tomography angiography (CTA) chest revealed a hematoma with an active extravasation within the right superior anterior mediastinum measuring 6 x 8 x 4 cm, outside the pericardium, and helped rule out hemopericardium. The imaging, just like in Figure 1, also showed that the posteriorly superior vena cava was compressed [4,5]. Due to the presence of hemorrhage adjuvant to epicardial pacer leads, it was proposed as a possible etiology for hemorrhage.…”
Section: Case Presentationmentioning
confidence: 93%
See 2 more Smart Citations
“…The differential diagnosis of a pericardial mass is challenging, and both benign and malignant (primary or metastatic) diseases should be considered [31]. Heterogenous non-neoplastic pericardial entities (hematomas, thrombi, pseudoaneurysms, cysts, and inflammatory pseudo tumours) are described in the literature [32], as is the contribution of multimodality imaging in the diagnosis of multiple pericardial hematomas and the development of progressive superior vena cava syndrome [33,34]. However, the literature to date has not described the presence of a pericardial haematoma secondary to chronic TAAD compressing the right atrium and the superior and inferior caval veins, leading to right heart failure.…”
Section: Discussionmentioning
confidence: 99%